Synthesis and Characterization of Polyimide Thin Films by Thermal Evaporation and Solid State Reactions (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: polyimide thin films; thermal imidization temperature; thermal evaporation; polycondensation reactions